Numerical study on engineering aspect of the cell geometries and flow channel design of Vanadium redox flow battery (V-RFB) - Suhailah, Sujali (2019)
This thesis presents the hydrodynamics behavior of the Vanadium redox flow battery (V-RFB) by using 3D computational fluid dynamics (CFD) models to study the pump power (pump energy consumption) and electrolyte flow distribution required within the cell. Pumping power and uniformity electrolyte flow are known as among the factors affecting a V-RFB cell performance. Among others, CFD is recognized as one of methods to study hydrodynamic characteristics of V-RFB. In this thesis, three different cell geometries of V-RFB cell, namely square-, rhombus- and circular cell designs are evaluated at three different cases i.e. no flow (plain) channel, parallel channel and serpentine channel. Furthermore, the work has been extended in modular stack of 100 cm2 of V-RFB. The stack has been developed and tested to observe the pump power within the stack in the three designs which directly related to performance of the cell with respect to power distribution and power losses. Based on the findings, the cell exhibits different characteristics under different geometries of V-RFB cell at no flow channel application. Conversely, based on the scaling up of the cell geometry, the relationship between pump power and cell geometry for 100 cm2 of V-RFB has been developed. Optimum flow distribution within the cells without fluid flow channels were recorded; highest and lowest pump consumption at 25.6% and 18.4% respectively. Extended reduction of power losses by 53 % were recorded as parallel flow channels was applied to the V-RFB. Proportionate correlations were observed for modular VRFB as a result of scaling up of the cell and potential for further analysis of extension to the nth-cell. Further works are presented for future research in geometry study of VRFB.